1998
DOI: 10.1021/ac970766q
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Association Constants between Drug Enantiomers and Human α1-Acid Glycoprotein by Applying a Partial-Filling Technique in Affinity Capillary Electrophoresis

Abstract: The principles for evaluation of conditional association constants between drug enantiomers and proteins, exemplified here by alpha 1-acid glycoprotein (AGP), using capillary zone electrophoresis employing a partial filling technique, is presented. In the partial filling technique only the first part of the capillary is filled with the selector, and this selector zone (plug) length can be varied by introducing the selector solution at different times at constant pressure. An important feature of the technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 39 publications
0
71
0
Order By: Relevance
“…Previously lectin ACE have been reported to demonstrate the usefulness in the determination of the specific structure of oligosaccharides, but the concentration, components and pH of the electrophoresis buffers have limited to sustain activity of the lectin used, and the usage of protein-containing buffers can complicate analyses due to adsorption of proteins to the capillary, vials and electrodes. A partial-filling ACE [23] can be used to overcome these situations. Fig.…”
Section: Partial Filling Affinity Capillary Electrophoresis For Glycamentioning
confidence: 99%
“…Previously lectin ACE have been reported to demonstrate the usefulness in the determination of the specific structure of oligosaccharides, but the concentration, components and pH of the electrophoresis buffers have limited to sustain activity of the lectin used, and the usage of protein-containing buffers can complicate analyses due to adsorption of proteins to the capillary, vials and electrodes. A partial-filling ACE [23] can be used to overcome these situations. Fig.…”
Section: Partial Filling Affinity Capillary Electrophoresis For Glycamentioning
confidence: 99%
“…The apparent mobility of drug in the presence of protein (µD,P) can be evaluated according to the following equation: 39,40 µD,P = X µ*DP + X µ*D + (1 -X)µD (1) where [ ] represents the molar concentration of each species in the solution. µ*D, µ*DP and µD are the mobility of free drug, drug-protein complex in the protein zone and that of free drug in the buffer zone, respectively.…”
Section: Determination Of the Association Constants Between Proteins mentioning
confidence: 99%
“…In a recent paper [1], the principles for determination of association constants between enantiomers of some basic drugs and a 1 -acid glycoprotein (AGP) as chiral selector by a partial filling technique (PFT) were described. PFT is a new separation mode initially employed for enantioseparations using a UV-absorbing chiral selector [2].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the plug length results in a reduction of the solute mobility, due to the longer interaction time between the selector and analyte. The degree of reduction is proportional to the affinity between the selector and the solute, and allows for determination of association constants [1]. It has also been shown that the enantioresolution is affected by the concentration of the chiral selector [17±19].…”
Section: Introductionmentioning
confidence: 99%